Artificial Reefs and People: How We Create Them and How They Affect Us - Lisa Chong; Keith Mille; Holly Abeels; Victor Blanco; Ed Camp (EDIS, 2021)
Artificial reefs are constructed to provide several important ecosystem services to coastal communities and fisheries around the world, and their deployment results in significant socio-ecological and economic effects. To understand these effects, this document gives an overview of the agencies and people involved in the use of artificial reefs, how the implementation of these reefs influences their perception, and what issues are associated with their deployment. This document also specifically describes the process by which most artificial reefs are implemented in Florida. While there is extensive research on ecological aspects of artificial reefs and reef fish, there is a need for more research on the effects of the implementation of artificial reefs on humans and the coastal communities and how their respective experiences and perceptions influence artificial reef and fisheries management actions and involvement.